Innate Immune Effectors Play Essential Roles in Acute Respiratory Infection Caused by Klebsiella pneumoniae - Dong Liu; Zhifu Chen; Yue Yuan; Haiming Jing; Jintao Zou; Xiaoli Zhang; Xi Zeng; Weijun Zhang; Quanming Zou; Jinyong Zhang (Journal of Immunology Research)
Innate immune effectors constitute the first line of host defense against pathogens. However, the roles of these effectors are not clearly defined during Klebsiella pneumoniae (K. pneumoniae) respiratory infection. In the current study, we established an acute pneumonia model of K. pneumoniae respiratory infection in mice and confirmed that the injury was most severe 48 h post infection. Flow cytometric assay demonstrated that alveolar macrophages were the predominant cells in BALF before infection, and neutrophils were quickly recruited after infection, and this was in consistent with the kinetics of chemokine expression. Further, we depleted neutrophils, macrophages, and complement pathways in vivo and challenged these mice with a sublethal dose of K. pneumonia, the result showed that 80%, 60%, and 40% of mice were died in these groups, respectively, while no deaths occurred in the control group. Besides, innate immune effector depleted mice showed higher bacterial burdens in lungs and blood, companied with more severe lung damage and increased levels of cytokine/chemokine expression. These results demonstrated that the innate immune effectors are critical in the early controlling of K. pneumoniae infection, and neutrophils are the most important. Thus, alternative strategies targeting these innate immune effectors may be effective in controlling of K. pneumoniae respiratory infection.